Laboratory wastewater treatment: Study case of Environmental Engineering Department ITS - Dyah Prasetyati Herrani; Nurhayati Ervin (BIO Web of Conferences)
Laboratory wastewater contains organic and inorganic pollutants that can pollute the environment if not treated well. This study uses a coagulation-flocculation process to determine the proper operational condition for laboratory wastewater treatment in the Environmental Engineering Department of Institut Teknologi Sepuluh Nopember (ITS). The fluctuation of wastewater quality and quantity was observed consecutively for two weeks. Aluminum sulfate, poly aluminum chloride, and ferric chloride coagulant were applied with a pH variation, namely 6, 7, and 8, and a variation in coagulant dosage, namely 100, 300, and 500 mg/L. The quantity of wastewater produced is in the range of 918.33-32,045 L/day. Meanwhile, for the quality of wastewater, it has a pH in the range of 6.23-8.79, TDS 260-788 mg/L, TSS 40-380 mg/L, COD 97-611.7 mg/L, Cr0.0174-0.2053 mg/L, Fe 0.29-7.55 mg/L, Hg 0-0.0000392 mg/L, and Pb 0-0.084 mg/L. The results of this study showed that the optimum condition for the coagulation-flocculation process is using PAC coagulant, with the original pH of the wastewater being pH 6 and the coagulant concentration being 300 mg/L. In this treatment, the removal efficiency of TDS, TSS, and COD were 7.07%, 92.59%, and 27.45%, respectively.